2004
DOI: 10.1081/agb-120037222
|View full text |Cite
|
Sign up to set email alerts
|

Resolutions of Facet Ideals

Abstract: Abstract. In this paper we study the resolution of a facet ideal associated with a special class of simplicial complexes introduced by Faridi. These simplicial complexes are called trees, and are a generalization (to higher dimensions) of the concept of a tree in graph theory. We show that the Koszul homology of the facet ideal I of a tree is generated by the homology classes of monomial cycles, determine the projective dimension and the regularity of I if the tree is 1-dimensional, show that the graded Betti … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
118
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(124 citation statements)
references
References 8 publications
6
118
0
Order By: Relevance
“…When restricted to simple graphs, Theorem 1.4(ii) also gives an interesting corollary, which was first proved by Zheng [33] in the special case that G was a forest. Corollary 1.7 (Corollary 6.9) Let G be a chordal graph.…”
Section: Theorem 11 (Theorem 32) Let H Be a Hypergraph With Two Or mentioning
confidence: 89%
See 1 more Smart Citation
“…When restricted to simple graphs, Theorem 1.4(ii) also gives an interesting corollary, which was first proved by Zheng [33] in the special case that G was a forest. Corollary 1.7 (Corollary 6.9) Let G be a chordal graph.…”
Section: Theorem 11 (Theorem 32) Let H Be a Hypergraph With Two Or mentioning
confidence: 89%
“…In the case that H is also triangulated, we explicitly compute reg(I(H)). Our exact formula for reg(I(H)) generalizes Zheng's formula [33] for the regularity of I(H) when H = G is a forest.…”
Section: Properly-connected Hypergraphs and Regularitymentioning
confidence: 97%
“…The connection between regularity and disconnected edges first appeared in Zheng's paper [17] and was extended to the case of chordal graphs in [10, Corollary 6.9]. Kummini showed that the conclusion to Corollary 3.10 is still true if is a bipartite graph whose edge ideal is unmixed.…”
Section: } Both Of Which Are Cohen-macaulay Bipartite Graphsmentioning
confidence: 91%
“…After that, hypergraph algebras have been widely studied. See for instance [5], [7], [10], [11], [12], [13], [14], [16], [19]. In [10], the authors use certain connectedness properties to determine a class of hypergraphs such that the hypergraph algebras have linear resolutions.…”
Section: (K ) ⊆ X (H ) and E (K ) ⊆ E (H ) If Y ⊆ X The Inducedmentioning
confidence: 99%